Temporal changes in the systemic concentrations of retinoids in pregnant and postpartum women. - Hyunyoung Jeong; Abigail T Armstrong; Nina Isoherranen; Lindsay Czuba; Amy Yang; Katelynn Zumpf; Jody Ciolino; Elizabeth Torres; Catherine S Stika; Katherine L Wisner (PLoS ONE, 2023)
Retinoids and vitamin A are essential for multiple biological functions, including vision and immune responses, as well as the development of an embryo during pregnancy. Despite its importance, alterations in retinoid homeostasis during normal human pregnancy are incompletely understood. We aimed to characterize the temporal changes in the systemic retinoid concentrations across pregnancy and postpartum period. Monthly blood samples were collected from twenty healthy pregnant women, and plasma concentrations of retinol, all-trans-retinoic acid (atRA), 13-cis-retinoic acid (13cisRA), and 4-oxo-retinoic acids were measured using liquid chromatography-tandem mass spectrometry. Significant decreases in 13cisRA concentrations over the pregnancy were observed, with rebound increases in retinol and 13cisRA levels after delivery. Of note, atRA concentrations exhibited a unique temporal pattern with levels peaking at mid-pregnancy. While the 4-oxo-atRA concentration was below the limit of quantification, 4-oxo-13cisRA was readily detectable, and its temporal change mimicked that of 13cisRA. The time profiles of atRA and 13cisRA remained similar after correction by albumin levels for plasma volume expansion adjustment. Together, the comprehensive profiling of systemic retinoid concentrations over the course of pregnancy provides insights into pregnancy-mediated changes in retinoid disposition to maintain its homeostasis.